Experimental investigation on anchor drop and drag - Xie, Clement Keqin (2009)
Marine and offshore industry has been growing significantly over the past few years. However due to the stellar growth in these industries, the risk of hazards pertaining to offshore pipelines damage by ship anchors inevitably rises. The significant damage to the pipeline may lead to severe environmental effect and risk to safety. It is therefore a major concern for marine engineers in the design of buried pipelines.